An ultra-low binder cemented carbide material for optical mold and a method for manufacturing the same
Patent Information
- Application Number
- CN202611255724.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-19
- Publication Date
- 2026-10-27
AI Technical Summary
[0003]现有技术中,硬质合金材料通常以碳化钨作为硬质相,并加入钴等金属粘结剂,通过压制成型及高温烧结使碳化钨颗粒在液相粘结作用下形成致密结构;然而,钴基粘结相的硬度及耐磨性能低于碳化钨硬质相,在光学模具长期使用及精密抛光过程中,容易影响材料表面的硬度均匀性和耐磨性能,因此,降低甚至取消钴基粘结剂的加入量逐渐成为高性能光学模具硬质合金材料的研究方向;但是,在缺少金属粘结相促进颗粒重排及致密化的情况下,碳化钨颗粒之间的烧结结合难度增大,容易残留较多孔隙,难以获得较高的致密程度;同时,为促进无钴或极低粘结剂硬质合金材料充分烧结,通常需要提高烧结温度或延长保温时间,而高温长时间烧结又容易造成碳化钨晶粒异常长大,使材料内部晶粒尺寸及组织分布不均,进而影响硬度、耐磨性能以及后续精密加工得到的表面质量
本发明在不添加钴基粘结剂的情况下,以碳化钨作为主要硬质相,并加入碳化钛、碳化钼、碳化铬及纳米碳粉共同改善烧结致密化及晶粒生长状态;通过对氮化钛粉体进行表面碳氮化处理,并进一步形成碳化钨包覆层,使所得改性氮化钛具有氮化钛核、碳氮化钛过渡层及碳化钨包覆层,能够减小氮化钛与碳化钨基体之间的界面组成差异,抑制烧结过程中碳化钨晶粒长大,并提高改性氮化钛与碳化钨基体之间的结合程度;同时,通过分阶段混合及改性氮化钛后加入的方式,提高微量组分在碳化钨粉体中的分散均匀性,并减少湿法球磨对改性氮化钛复合界面结构的破坏;结合低轴向载荷脉冲预热排气及根据烧结粉体轴向收缩状态进行分级加压的SPS烧结方式,可促进残余气体排出及孔隙闭合,并协调升温、颗粒收缩及压力致密化过程,从而在抑制碳化钨晶粒长大的同时提高材料的致密程度,以得到孔隙少且力学性能良好的光学模具用极低粘结剂硬质合金材料。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of cemented carbide materials, and more particularly to an ultra-low binder cemented carbide material for optical molds and its preparation method. Background Technology
[0002] Hard alloy materials for optical molds are used to manufacture molds for precision optical components such as optical glass and optical lenses. They typically need to have high hardness, wear resistance, density, and fine and uniform grain structure to ensure that the molds have good surface quality and service life during high-temperature molding and repeated use.
[0003] In existing technologies, cemented carbide materials typically use tungsten carbide as the hard phase and add metal binders such as cobalt. Through pressing and high-temperature sintering, tungsten carbide particles form a dense structure under liquid-phase bonding. However, the hardness and wear resistance of the cobalt-based binder phase are lower than those of the tungsten carbide hard phase. During long-term use and precision polishing of optical molds, this can easily affect the surface hardness uniformity and wear resistance. Therefore, reducing or even eliminating the amount of cobalt-based binder has gradually become a research direction for high-performance optical mold cemented carbide materials. However, without a metal binder phase to promote particle rearrangement and densification, the sintering bonding between tungsten carbide particles becomes more difficult, easily leaving more pores and making it difficult to achieve a high degree of density. Simultaneously, to promote the full sintering of cobalt-free or very low-binder cemented carbide materials, it is usually necessary to increase the sintering temperature or extend the holding time. However, high-temperature, long-term sintering can easily cause abnormal growth of tungsten carbide grains, resulting in uneven grain size and microstructure distribution within the material, thus affecting hardness, wear resistance, and the surface quality obtained from subsequent precision machining.
[0004] Therefore, existing technologies have shortcomings and need to be improved. Summary of the Invention
[0005] The technical problem to be solved by the present invention is to provide a method for preparing an ultra-low binder hard alloy material for optical molds with high density, few pore defects, and fine grains.
[0006] To achieve this objective, the present invention adopts the following technical solution: an ultra-low binder hard alloy material for optical molds and its preparation method, comprising the following steps: S1. Weigh out 0.2-0.4% titanium carbide powder, 0.2-0.4% titanium nitride powder, 0.05-0.15% molybdenum carbide powder, 0.03-0.10% chromium carbide powder, 0.03-0.08% nano carbon powder, and the balance tungsten carbide powder by mass percentage. S2. Titanium nitride powder is placed in a carbon-containing atmosphere for surface carbonitriding treatment to form a titanium carbonitride transition layer on the surface of titanium nitride particles; then the surface carbonitrided titanium nitride powder is dispersed, and a tungsten source precursor and an auxiliary carbon source are added so that the tungsten source precursor is attached to the surface of the titanium carbonitride transition layer. After drying, reduction and carbonization treatment, a tungsten carbide coating layer is formed to obtain modified titanium nitride. S3. Take 15-30% of the total mass of tungsten carbide powder and premix it with titanium carbide powder, molybdenum carbide powder and chromium carbide powder to obtain a first premix; mix the first premix with the remaining 70-85% of tungsten carbide powder and nano carbon powder to obtain a mixed powder. S4. The mixed powder obtained in step S3 is subjected to wet ball milling. After ball milling, the modified titanium nitride obtained in step S2 is added and mixed. Then, the mixture is degassed, dried and sieved to obtain sintered powder. S5. The sintered powder is loaded into a graphite mold, and the graphite mold is placed in a spark plasma sintering equipment for pulse preheating and degassing under vacuum and low axial load conditions. S6. After completing the pulse preheating and exhaust in step S5, SPS sintering is carried out by segmented heating. The axial load is gradually increased according to the axial shrinkage state of the sintered powder. When the sintering temperature reaches 1700℃, the axial load is increased to 35kN and held at 1700℃ and 35kN for 20min. S7. After completing the SPS sintering in step S6, stop heating and cool down while maintaining the axial load. Gradually remove the axial load as the temperature decreases. After cooling and demolding, obtain the ultra-low binder hard alloy material for optical molds.
[0007] Using the above technical solution, in step S1, the D50 particle size of the tungsten carbide powder is 0.25-0.45 μm, the D50 particle size of the titanium carbide powder is 0.08-0.20 μm, the D50 particle size of the titanium nitride powder is 0.05-0.15 μm, the D50 particle size of the molybdenum carbide powder is 0.05-0.15 μm, the D50 particle size of the chromium carbide powder is 0.05-0.15 μm, and the D50 particle size of the nano-carbon powder is 30-100 nm. Before mixing, tungsten carbide powder, titanium carbide powder, titanium nitride powder, molybdenum carbide powder and chromium carbide powder were dried in a vacuum environment at 110-140℃ for 2-5 hours, and then cooled to below 40℃ in a vacuum or high-purity argon environment and sealed for storage.
[0008] Using the above technical solution, in the surface carbonitriding process of step S2, titanium nitride powder is placed in an atmosphere furnace, and a mixed gas composed of methane, hydrogen and argon is introduced into the atmosphere furnace, wherein the volume ratio of methane, hydrogen and argon is 1:3-6:8-15. The temperature is increased to 850-1000℃ at a heating rate of 3-8℃ / min, and held at 850-1000℃ for 30-90min, so that the carbon elements produced by the decomposition of methane diffuse from the surface of the titanium nitride particles inward, and the surface layer of the titanium nitride particles is partially transformed to form a titanium carbonitride transition layer. The thickness of the titanium carbonitride transition layer is 3-15 nm.
[0009] Using the above technical solution, in the dispersion and tungsten-containing precursor coating process of step S2, the titanium nitride powder forming the titanium carbonitride transition layer is added to a mixture of anhydrous ethanol and deionized water, wherein the volume ratio of anhydrous ethanol to deionized water is 4-7:1, the mass fraction of titanium nitride powder in the obtained titanium nitride dispersion is 3-8%, and 0.3-0.8% of ammonium polyacrylate is added, and the mixture is sheared and dispersed at 1000-2000 rpm for 10-30 min, and then ultrasonically dispersed for 20-40 min. Ammonium metatungstate is added to the obtained dispersion as a tungsten source precursor, wherein the mass of tungsten in the ammonium metatungstate is 5-12% of the mass of the titanium nitride powder. Then glucose is added as an auxiliary carbon source, wherein the mass of glucose added is 10-18% of the mass of the ammonium metatungstate. The mixture is stirred at 300-800 rpm for 30-90 min at 50-70℃ to allow the tungsten source precursor and auxiliary carbon source to adhere to the surface of the titanium carbonitride transition layer. After mixing, the mixture is spray-dried to obtain composite titanium nitride powder with a tungsten-containing precursor coating layer.
[0010] Using the above technical solution, in the reduction and carbonization process of step S2, the composite titanium nitride powder is placed in an atmosphere furnace and heated to 500-650°C at a heating rate of 3-8°C / min under the protection of high-purity argon gas and held for 30-90min to allow the auxiliary carbon source to undergo pyrolysis. Subsequently, the temperature was raised to 650-800℃ and held for 1-2 hours in a reducing atmosphere composed of hydrogen and argon to reduce the tungsten source precursor in the tungsten-containing precursor coating layer to form tungsten-based particles. After the reduction treatment is completed, the temperature is raised to 900-1050℃ and a mixed gas of methane and hydrogen is introduced for carbonization treatment for 0.5-2 hours, so that the tungsten-based particles are transformed into tungsten carbide coating layer, so as to obtain modified titanium nitride with titanium nitride core, titanium carbonitride transition layer and tungsten carbide coating layer from the inside to the outside. The tungsten carbide coating has an average thickness of 5-25 nm, the volume ratio of hydrogen to argon is 1:2-5, and the volume ratio of methane to hydrogen is 1:4-10.
[0011] Using the above technical solution, in step S3, 15-30% of the total mass of tungsten carbide powder is taken, and the tungsten carbide powder is premixed with titanium carbide powder, molybdenum carbide powder and chromium carbide powder at 20-50 rpm for 30-60 min to obtain the first premix. The first premixed material is mixed with the remaining 70-85% of tungsten carbide powder and nano carbon powder at 30-60 rpm for 30-90 min to obtain the mixed powder. In step S4, anhydrous ethanol is added to the mixed powder as a ball milling medium, and tungsten carbide balls are used as the grinding medium. The liquid-solid mass ratio between the anhydrous ethanol and the mixed powder is 0.6-1.0:1, and the ball-to-powder mass ratio is 3-5:1. Wet ball milling is carried out at 120-180 rpm for 2-5 hours. After wet ball milling, add the modified titanium nitride, reduce the speed to 50-90 rpm and continue mixing for 30-90 min to disperse the modified titanium nitride between the tungsten carbide particles. After mixing, the resulting slurry is vacuum degassed for 10-30 minutes, then spray-dried, and the resulting powder is dried in a vacuum environment at 80-110℃ for 4-8 hours. Subsequently, it is sieved through a 100-200 mesh sieve to obtain the sintered powder.
[0012] Using the above technical solution, in step S5, the sintered powder is loaded into the graphite mold in 2-4 batches. After each addition of sintered powder, vibration leveling is performed. After the loading is completed, an axial preload of 2-5kN is applied and held for 1-3 minutes. The sintering chamber of the spark plasma sintering equipment is evacuated to below 20 Pa, and preheated by applying pulsed DC current under an axial load of 2-5 kN. During the temperature rise from room temperature to 500℃, the temperature is increased at a rate of 60-100℃ / min. After the temperature reaches 500℃, the temperature is increased to 850-950℃ at a rate of 70-110℃ / min, and held at 850-950℃ for 3-8 minutes, while maintaining the pressure in the sintering chamber at 5-20Pa. During the pulse preheating and venting process, the axial displacement of the pressure head on the graphite mold is monitored. Before the sintered powder produces continuous axial shrinkage, the axial load is maintained at 2-5 kN to allow the residual gas in the sintered powder to be discharged outward.
[0013] Using the above technical solution, in step S6, the SPS sintering adopts a graded pressurization method based on the axial shrinkage state: The sintering temperature was further increased from 850-950℃ to 1100-1250℃. When continuous axial displacement of the pressure head on the graphite mold was detected, the axial load was gradually increased to 6-10kN. Then, the temperature was increased to 1400℃ at a heating rate of 60-90℃ / min, and the axial load was gradually increased to 12-18kN. In the 1400-1550℃ range, the heating rate was controlled at 40-60℃ / min, and the axial load was gradually increased to 20-25kN. In the 1550-1650℃ range, the heating rate was reduced to 25-45℃ / min, and the axial load was gradually increased to 28-32kN. After the sintering temperature reaches 1650℃, the temperature is further increased to 1700℃ at a heating rate of 15-30℃ / min, and the axial load is simultaneously increased to 35kN. The temperature is then maintained at 1700℃ and 35kN for 20 minutes to allow the residual pores in the sintered powder to shrink and close.
[0014] Using the above technical solution, in step S7, after SPS sintering at 1700℃ and 35kN is completed, the heating is stopped, and the axial load of 35kN is maintained for cooling. When the temperature drops to 1550-1600℃, the first pressure relief is carried out to reduce the axial load to 20-25kN, and the cooling process continues. When the temperature drops to 1350-1450℃, a second depressurization is performed to reduce the axial load to 8-12kN, and cooling continues. When the temperature drops to 1100-1200℃, the axial load is completely removed, and high-purity argon gas is introduced into the sintering chamber. The temperature is then reduced to 800℃ at a cooling rate of 2-5℃ / min, and then reduced to 500℃ at a cooling rate of 5-10℃ / min. Subsequently, the temperature is cooled to room temperature with the furnace. After demolding, the ultra-low binder hard alloy material for the optical mold is obtained.
[0015] This technical solution also provides an ultra-low binder cemented carbide material for optical molds, which is prepared by any of the above-mentioned preparation methods. The ultra-low binder cemented carbide material for optical molds does not contain cobalt-based binders, has a relative density greater than 99%, a porosity grade of A02B00, and an average tungsten carbide grain size of no more than 0.6 μm.
[0016] Compared with the prior art, the present invention has the following beneficial effects: This invention uses tungsten carbide as the main hard phase without adding a cobalt-based binder, and incorporates titanium carbide, molybdenum carbide, chromium carbide, and nano-carbon powder to improve sintering densification and grain growth. By performing surface carbonitriding treatment on titanium nitride powder and further forming a tungsten carbide coating layer, the resulting modified titanium nitride possesses a titanium nitride core, a titanium carbonitride transition layer, and a tungsten carbide coating layer. This reduces the difference in interfacial composition between titanium nitride and the tungsten carbide matrix, inhibits tungsten carbide grain growth during sintering, and improves the bonding between the modified titanium nitride and the tungsten carbide matrix. Simultaneously, through… The phased mixing and subsequent addition of modified titanium nitride improves the dispersion uniformity of trace components in tungsten carbide powder and reduces the damage to the composite interface structure of modified titanium nitride caused by wet ball milling. Combined with the SPS sintering method of low axial load pulse preheating and venting and staged pressurization according to the axial shrinkage state of the sintered powder, residual gas discharge and pore closure can be promoted, and the heating, particle shrinkage and pressure densification processes can be coordinated. This can improve the density of the material while inhibiting the growth of tungsten carbide grains, so as to obtain an ultra-low binder cemented carbide material for optical molds with low porosity and good mechanical properties. Detailed Implementation
[0017] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are merely illustrative of the invention and are not intended to limit the invention. Furthermore, the terms "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., described below refer to specific features, structures, materials, or characteristics described in connection with that embodiment or example, which are included in at least one embodiment or example of the invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Moreover, the technical features involved in the various embodiments of the invention can be combined with each other as long as they do not conflict with each other.
[0018] Example 1 Embodiment 1 of the present invention provides a method for preparing an ultra-low binder hard alloy material for optical molds, comprising the following steps: S1. Raw material preparation and pretreatment: Weigh out 0.30% titanium carbide powder, 0.30% titanium nitride powder, 0.10% molybdenum carbide powder, 0.06% chromium carbide powder, 0.05% nano-carbon powder, and 99.19% tungsten carbide powder by mass percentage, with the sum of the mass percentages of each component being 100%; wherein, the D50 particle size of the tungsten carbide powder is 0.35 μm, the D50 particle size of the titanium carbide powder is 0.14 μm, and the D50 particle size of the titanium nitride powder is... The D50 particle size of the titanium carbide powder is 0.10 μm, the D50 particle size of the molybdenum carbide powder is 0.10 μm, the D50 particle size of the chromium carbide powder is 0.10 μm, and the D50 particle size of the nano-carbon powder is 60 nm. Before mixing, the tungsten carbide powder, titanium carbide powder, titanium nitride powder, molybdenum carbide powder, and chromium carbide powder were dried in a vacuum environment at 125°C for 3 hours, and then cooled to 35°C in a high-purity argon environment and sealed for storage. S2. Preparation of modified titanium nitride: The titanium nitride powder obtained in step S1 is placed in an atmosphere furnace, and a mixed gas composed of methane, hydrogen and argon is introduced into the atmosphere furnace. The volume ratio of methane, hydrogen and argon is 1:4:10. The temperature is raised to 920℃ at a heating rate of 5℃ / min and held at 920℃ for 60min. This allows the carbon elements produced by the decomposition of methane to diffuse from the surface of the titanium nitride particles inward, so that the surface layer of the titanium nitride particles is partially transformed to form a titanium carbonitride transition layer with a thickness of 8nm. Titanium nitride powder forming the titanium carbonitride transition layer was added to a mixture of anhydrous ethanol and deionized water at a volume ratio of 5:1, resulting in a titanium nitride dispersion with a titanium nitride powder mass fraction of 5%. Then, ammonium polyacrylate (0.5% by mass of titanium nitride powder) was added, and the mixture was sheared and dispersed at 1500 rpm for 20 min, followed by ultrasonic dispersion for 30 min. Ammonium metatungstate was added to the resulting dispersion as a tungsten source precursor, with the tungsten element in the ammonium metatungstate comprising 8% of the titanium nitride powder mass. Glucose was then added as an auxiliary carbon source, with the glucose content being 14% of the ammonium metatungstate mass. The mixture was stirred at 500 rpm for 60 min at 60°C to allow the tungsten source precursor and auxiliary carbon source to adhere to the surface of the titanium carbonitride transition layer. After mixing, the mixture was spray-dried to obtain a composite titanium nitride powder with a tungsten-containing precursor coating layer. The composite titanium nitride powder was placed in an atmosphere furnace and heated to 580°C at a rate of 5°C / min under the protection of high-purity argon, and held for 60 min to allow the auxiliary carbon source to pyrolyze. Subsequently, the temperature was further increased to 720°C and held for 1.5 h in a reducing atmosphere composed of hydrogen and argon, with a volume ratio of hydrogen to argon of 1:3, to reduce the tungsten source precursor in the tungsten-containing precursor coating layer to form tungsten-based particles. After the reduction treatment, the temperature was further increased to 980°C, and a mixed gas composed of methane and hydrogen was introduced for carbonization treatment for 1 h, with a volume ratio of methane to hydrogen of 1:6, to convert the tungsten-based particles into a tungsten carbide coating layer, thereby obtaining modified titanium nitride with a titanium nitride core, a titanium carbonitride transition layer, and a tungsten carbide coating layer from the inside out. The average thickness of the tungsten carbide coating layer was 15 nm. S3. Preparation of mixed powder: Take 20% of the total mass of tungsten carbide powder obtained in step S1, and premix the tungsten carbide powder with titanium carbide powder, molybdenum carbide powder and chromium carbide powder at 35 rpm for 45 min to obtain a first premix; then mix the first premix with the remaining 80% of tungsten carbide powder and nano carbon powder at 45 rpm for 60 min to disperse titanium carbide powder, molybdenum carbide powder, chromium carbide powder and nano carbon powder in tungsten carbide powder to obtain mixed powder; S4. Preparation of sintered powder: Anhydrous ethanol is added to the mixed powder obtained in step S3 as a ball milling medium, and tungsten carbide balls are used as the grinding medium. The liquid-solid mass ratio between the anhydrous ethanol and the mixed powder is 0.8:1, and the ball-to-powder mass ratio is 4:1. Wet ball milling is performed at 150 rpm for 4 hours. After wet ball milling, the modified titanium nitride obtained in step S2 is added, the speed is reduced to 70 rpm, and mixing continues for 60 minutes to disperse the modified titanium nitride between the tungsten carbide particles. After mixing, the resulting slurry is vacuum degassed for 20 minutes, then spray dried, and the resulting powder is dried in a vacuum environment at 95°C for 6 hours. Finally, it is sieved through a 150-mesh sieve to obtain sintered powder. S5. Mold Loading and Pulse Preheating Exhaust: The sintered powder obtained in step S4 is loaded into the graphite mold in three batches. After each addition of sintered powder, vibration leveling is performed. After all the sintered powder is loaded, an axial preload of 3 kN is applied to the sintered powder and held for 2 min. Then, the graphite mold is placed in the spark plasma sintering equipment, the sintering chamber is evacuated to 10 Pa, and pulsed DC current is applied under an axial load of 3 kN for preheating. In the stage from room temperature to 500°C, the temperature is increased at a rate of 80°C / min. When the temperature reaches 500°C, the temperature is increased to 900°C at a rate of 90°C / min and held at 900°C for 5 min, while the pressure in the sintering chamber is maintained at 10 Pa. During the pulse preheating exhaust process, the axial displacement of the pressure head on the graphite mold is monitored. Before the sintered powder produces continuous axial shrinkage, the axial load is maintained at 3 kN to allow the residual gas in the sintered powder to be discharged. S6. SPS Segmented Heating and Staged Pressurized Sintering: After completing the pulse preheating and venting in step S5, the sintering temperature is further increased from 900℃ to 1200℃, and the axial load is gradually increased according to the axial shrinkage state of the sintered powder. When continuous axial displacement of the pressure head on the graphite mold is detected, the axial load is gradually increased to 8kN; then, the temperature is further increased to 1400℃ at a heating rate of 75℃ / min, and the axial load is gradually increased to 15kN; in the 1400-1550℃ stage, the heating rate is controlled... The heating rate was initially set at 50℃ / min, and the axial load was gradually increased to 22kN. In the 1550-1650℃ range, the heating rate was reduced to 35℃ / min, and the axial load was gradually increased to 30kN. When the sintering temperature reached 1650℃, the temperature was increased to 1700℃ at a rate of 20℃ / min, and the axial load was simultaneously increased to 35kN. The temperature was then maintained at 1700℃ and 35kN for 20 minutes to allow the residual pores in the sintered powder to shrink and close, thereby completing the densification of the sintered powder. S7. Staged depressurization and cooling: After SPS sintering at 1700℃ and 35kN in step S6, the heating is stopped, and the axial load of 35kN is maintained for cooling. When the temperature drops to 1575℃, the first depressurization is performed to reduce the axial load to 22kN, and the cooling continues. When the temperature drops to 1400℃, the second depressurization is performed to reduce the axial load to 10kN, and the cooling continues. When the temperature drops to 1150℃, the axial load is completely removed, and high-purity argon gas is introduced into the sintering chamber. The temperature is reduced to 800℃ at a cooling rate of 3℃ / min, and then reduced to 500℃ at a cooling rate of 8℃ / min. Subsequently, the furnace is cooled to room temperature. After demolding, the ultra-low binder hard alloy material for optical molds is obtained. Testing revealed that the obtained optical mold ultra-low binder cemented carbide material does not contain cobalt-based binders, has a relative density of 99.5%, a porosity grade of A02B00, and an average tungsten carbide grain size of 0.58 μm.
[0019] Example 2 Embodiment 2 of the present invention provides an ultra-low binder hard alloy material for optical molds and its preparation method, comprising the following steps: S1. Raw material preparation and pretreatment: Weigh out 0.36% titanium carbide powder, 0.24% titanium nitride powder, 0.13% molybdenum carbide powder, 0.08% chromium carbide powder, 0.07% nano-carbon powder, and 99.12% tungsten carbide powder by mass percentage, with the sum of the mass percentages of each component being 100%; wherein, the D50 particle size of the tungsten carbide powder is 0.40 μm, the D50 particle size of the titanium carbide powder is 0.18 μm, and the... The titanium nitride powder has a D50 particle size of 0.08 μm, the molybdenum carbide powder has a D50 particle size of 0.12 μm, the chromium carbide powder has a D50 particle size of 0.07 μm, and the nano-carbon powder has a D50 particle size of 80 nm. Before mixing, the tungsten carbide powder, titanium carbide powder, titanium nitride powder, molybdenum carbide powder, and chromium carbide powder were dried in a vacuum environment at 135°C for 4 hours, and then cooled to 30°C in a vacuum environment and sealed for storage. S2. Preparation of modified titanium nitride: The titanium nitride powder obtained in step S1 is placed in an atmosphere furnace, and a mixed gas composed of methane, hydrogen and argon is introduced into the atmosphere furnace. The volume ratio of methane, hydrogen and argon is 1:5:12. The temperature is raised to 980℃ at a heating rate of 7℃ / min and held at 980℃ for 75min. This allows the carbon elements produced by the decomposition of methane to diffuse from the surface of the titanium nitride particles inward, so that the surface layer of the titanium nitride particles is partially transformed to form a titanium carbonitride transition layer with a thickness of 12nm. Titanium nitride powder forming the titanium carbonitride transition layer was added to a mixture of anhydrous ethanol and deionized water at a volume ratio of 6:1, resulting in a titanium nitride dispersion with a titanium nitride powder mass fraction of 7%. Then, ammonium polyacrylate (0.7% by mass of the titanium nitride powder) was added, and the mixture was sheared and dispersed at 1800 rpm for 25 min, followed by ultrasonic dispersion for 35 min. Ammonium metatungstate was added to the resulting dispersion as a tungsten source precursor, with the tungsten content in the ammonium metatungstate being 10% of the titanium nitride powder mass. Glucose was then added as an auxiliary carbon source, with the glucose content being 16% of the ammonium metatungstate mass. The mixture was stirred at 700 rpm for 75 min at 65°C to allow the tungsten source precursor and auxiliary carbon source to adhere to the surface of the titanium carbonitride transition layer. After mixing, the mixture was spray-dried to obtain a composite titanium nitride powder with a tungsten-containing precursor coating layer. The composite titanium nitride powder was placed in an atmosphere furnace and heated to 620°C at a rate of 7°C / min under the protection of high-purity argon, and held for 75 min to allow the auxiliary carbon source to pyrolyze. Subsequently, the temperature was further increased to 780°C and held for 2 h in a reducing atmosphere composed of hydrogen and argon, with a volume ratio of hydrogen to argon of 1:4, to reduce the tungsten source precursor in the tungsten-containing precursor coating layer to form tungsten-based particles. After the reduction treatment, the temperature was further increased to 1030°C, and a mixed gas composed of methane and hydrogen was introduced for carbonization treatment for 1.5 h, with a volume ratio of methane to hydrogen of 1:8, to convert the tungsten-based particles into a tungsten carbide coating layer, thereby obtaining modified titanium nitride with a titanium nitride core, a titanium carbonitride transition layer, and a tungsten carbide coating layer from the inside out. The average thickness of the tungsten carbide coating layer was 20 nm. S3. Preparation of mixed powder: Take 25% of the total mass of tungsten carbide powder obtained in step S1, and premix the tungsten carbide powder with titanium carbide powder, molybdenum carbide powder and chromium carbide powder at 45 rpm for 55 min to obtain a first premix; then mix the first premix with the remaining 75% of tungsten carbide powder and nano carbon powder at 55 rpm for 80 min to disperse titanium carbide powder, molybdenum carbide powder, chromium carbide powder and nano carbon powder in tungsten carbide powder to obtain mixed powder; S4. Preparation of sintered powder: Anhydrous ethanol is added to the mixed powder obtained in step S3 as a ball milling medium, and tungsten carbide balls are used as the grinding medium. The liquid-solid mass ratio between the anhydrous ethanol and the mixed powder is 1.0:1, and the ball-to-powder mass ratio is 5:1. Wet ball milling is performed at 170 rpm for 5 h. After wet ball milling, the modified titanium nitride obtained in step S2 is added, the speed is reduced to 90 rpm, and mixing continues for 75 min to disperse the modified titanium nitride between the tungsten carbide particles. After mixing, the resulting slurry is vacuum degassed for 25 min, then spray dried, and the resulting powder is dried in a vacuum environment at 105℃ for 7 h. Then it is sieved through an 180-mesh sieve to obtain sintered powder. S5. Mold Loading and Pulse Preheating Exhaust: The sintered powder obtained in step S4 is loaded into the graphite mold in four batches. After each addition of sintered powder, vibration leveling is performed. After all the sintered powder is loaded, an axial preload of 5 kN is applied to the sintered powder and held for 3 min. Then, the graphite mold is placed in the spark plasma sintering equipment, the sintering chamber is evacuated to 15 Pa, and pulsed DC current is applied under an axial load of 5 kN for preheating. In the stage from room temperature to 500°C, the temperature is increased at a rate of 95°C / min. When the temperature reaches 500°C, the temperature is increased to 950°C at a rate of 105°C / min and held at 950°C for 7 min, while the pressure in the sintering chamber is maintained at 15 Pa. During the pulse preheating exhaust process, the axial displacement of the pressure head on the graphite mold is monitored. Before the sintered powder produces continuous axial shrinkage, the axial load is maintained at 5 kN to allow the residual gas in the sintered powder to be discharged. S6. SPS Segmented Heating and Staged Pressurized Sintering: After completing the pulse preheating and venting in step S5, the sintering temperature is further increased from 950℃ to 1250℃, and the axial load is gradually increased according to the axial shrinkage state of the sintered powder. When continuous axial displacement of the pressure head on the graphite mold is detected, the axial load is gradually increased to 10kN; then, the temperature is further increased to 1400℃ at a heating rate of 85℃ / min, and the axial load is gradually increased to 18kN; in the 1400-1550℃ stage, the heating rate is controlled... The heating rate was set at 60℃ / min, and the axial load was gradually increased to 25kN. In the 1550-1650℃ stage, the heating rate was reduced to 45℃ / min, and the axial load was gradually increased to 32kN. When the sintering temperature reached 1650℃, the temperature was continued to rise to 1700℃ at a heating rate of 30℃ / min, and the axial load was simultaneously increased to 35kN. The temperature was held at 1700℃ and 35kN for 20 minutes to shrink and close the residual pores in the sintered powder, thereby completing the densification of the sintered powder. S7. Staged depressurization and cooling: After SPS sintering at 1700℃ and 35kN in step S6, the heating is stopped, and the axial load of 35kN is maintained for cooling. When the temperature drops to 1600℃, the first depressurization is performed to reduce the axial load to 25kN, and the cooling continues. When the temperature drops to 1450℃, the second depressurization is performed to reduce the axial load to 12kN, and the cooling continues. When the temperature drops to 1200℃, the axial load is completely removed, and high-purity argon gas is introduced into the sintering chamber. The temperature is reduced to 800℃ at a cooling rate of 5℃ / min, and then reduced to 500℃ at a cooling rate of 10℃ / min. Subsequently, the furnace is cooled to room temperature. After demolding, the ultra-low binder hard alloy material for optical molds is obtained.
[0020] Testing revealed that the obtained optical mold ultra-low binder cemented carbide material does not contain cobalt-based binders, has a relative density of 99.3%, a porosity grade of A02B00, and an average tungsten carbide grain size of 0.55μm.
[0021] Comparative Example 1 The difference between the ultra-low binder hard alloy material for optical molds and its preparation method in Comparative Example 1 and Example 1 is that in step S2, the titanium nitride powder is not subjected to surface carbonitriding treatment and subsequent tungsten-containing precursor coating, reduction and carbonization treatment. Instead, unmodified titanium nitride powder is used directly for subsequent mixing and SPS sintering.
[0022] Comparative Example 2 The difference between the ultra-low binder hard alloy material for optical molds and its preparation method in Comparative Example 2 and Example 1 is that in step S2, only the surface carbonitriding treatment of titanium nitride powder is performed, without subsequent tungsten-containing precursor coating, reduction and carbonization treatment, that is, no tungsten carbide coating layer is formed.
[0023] Comparative Example 3 The difference between the ultra-low binder hard alloy material for optical molds and its preparation method in Comparative Example 3 and Example 1 is that: in step S2, the titanium nitride powder is not subjected to surface carbonitriding treatment, but the titanium nitride powder without surface carbonitriding treatment is directly coated with tungsten-containing precursor, reduced and carbonized, so that the tungsten carbide coating layer is directly formed on the surface of the titanium nitride particles.
[0024] Comparative Example 4 The difference between the ultra-low binder hard alloy material for optical molds and its preparation method in Comparative Example 4 and Example 1 is that in steps S3 and S4, tungsten carbide powder, titanium carbide powder, molybdenum carbide powder, chromium carbide powder, nano carbon powder and modified titanium nitride are mixed at one time and wet ball-milled at 150 rpm for 4 hours.
[0025] Comparative Example 5 The difference between the ultra-low binder hard alloy material for optical molds and its preparation method in Comparative Example 5 and Example 1 is that: in step S5, pulse preheating and venting treatment is not performed. Instead, after the sintering powder is loaded into the graphite mold and the sintering cavity is evacuated, the temperature is directly increased while maintaining an axial load of 3kN to enter the subsequent SPS sintering process.
[0026] Comparative Example 6 The difference between the ultra-low binder hard alloy material for optical molds and its preparation method in Comparative Example 6 and Example 1 is that: in step S6, instead of graded pressurization based on the axial shrinkage state of the sintered powder, the axial load is directly increased to 35kN after the pulse preheating and venting in step S5, and the axial load of 35kN is maintained during the subsequent heating process until the temperature reaches 1700℃ and is held for 20min.
[0027] To verify the effects of the preparation method of this invention on the density, porosity control, tungsten carbide grain refinement, mechanical properties, and mirror finish quality of ultra-low binder cemented carbide materials for optical molds, performance tests were conducted on the ultra-low binder cemented carbide materials for optical molds prepared in Examples 1-2 and Comparative Examples 1-6. The test items included relative density, porosity grade, average WC grain size, Vickers hardness, flexural strength, and surface roughness Ra after mirror polishing. Before testing, the surfaces of each group of samples were cleaned and dried at 120℃ for 2 hours, then cooled to room temperature. All properties were tested under the same sample preparation and testing conditions. Three samples were taken from each group, and the average value was calculated. The test results are shown in Table 1.
[0028] Table 1. Performance Comparison of Ultra-Low Binder Hard Alloy Materials for Optical Molds According to Table 1 above, in the ultra-low binder hard alloy materials for optical molds prepared in Examples 1 and 2, this invention uses tungsten carbide as the main hard phase without adding cobalt-based binders, and adds titanium carbide, molybdenum carbide, chromium carbide, and nano-carbon powder to improve sintering densification and grain growth. Specifically, the titanium nitride powder undergoes surface carbonitriding treatment to form a titanium carbonitriding transition layer on the surface of the titanium nitride particles. Then, through tungsten source precursor attachment, reduction, and carbonization treatment, a carbonitriding... A tungsten carbide coating is formed outside the titanium transition layer to obtain modified titanium nitride composed of a titanium nitride core, a titanium carbonitride transition layer, and a tungsten carbide coating layer. The titanium carbonitride transition layer can reduce the abrupt change in the interface composition between titanium nitride and the tungsten carbide matrix and inhibit the migration of tungsten carbide grain boundaries during sintering. The external tungsten carbide coating layer makes it easier for the modified titanium nitride to form a continuous contact interface with the tungsten carbide matrix during initial mixing and sintering, thereby taking into account the uniform dispersion of the second phase, the inhibition of grain growth, and the interparticle bonding.
[0029] Meanwhile, this invention first premixes a portion of tungsten carbide powder with titanium carbide powder, molybdenum carbide powder, and chromium carbide powder, and then mixes it with the remaining tungsten carbide powder and nano-carbon powder. This allows the auxiliary components, which have a lower content, to be dispersed among the tungsten carbide powder particles before diffusing into the entire powder system. After wet ball milling of the main powder, modified titanium nitride is added and mixed at low speed. This reduces the damage to the titanium carbonitride transition layer and tungsten carbide coating layer caused by prolonged wet ball milling, and helps maintain the composite interface structure and dispersion state of the modified titanium nitride. Subsequently, pulse preheating and venting with low axial load were used before SPS sintering to remove residual gas between particles before the sintered powder had significantly shrunk and densified. During the subsequent SPS sintering process, the axial load was gradually increased according to the axial shrinkage state of the sintered powder, so that the heating, particle shrinkage and pressure densification processes were coordinated with each other, and finally rapid densification was completed at 1700℃ and 35kN. This helped to reduce residual porosity and avoid applying large loads too early at lower temperatures, which could cause local pore closure and uneven microstructure.
[0030] Therefore, the ultra-low binder cemented carbide materials for optical molds prepared in Examples 1 and 2 both have high relative density, porosity level of A02B00, and average tungsten carbide grain size controlled at a low level. They also have high Vickers hardness and bending strength, and low surface roughness Ra after mirror polishing. This indicates that the present invention can achieve densification, porosity control, grain refinement and mirror finish quality of cemented carbide materials without adding cobalt-based binders.
[0031] In Comparative Example 1, the titanium nitride powder was not subjected to surface carbonitriding treatment or subsequent tungsten-containing precursor coating, reduction, and carbonization treatment. Instead, unmodified ordinary titanium nitride powder was directly used for subsequent mixing and SPS sintering. This resulted in the lack of a titanium carbonitride transition layer and a tungsten carbide coating layer between the titanium nitride particles and the tungsten carbide matrix, making it difficult to fully exert the interfacial transition and grain boundary inhibition effects. At the same time, the dispersion and interfacial bonding effect of ordinary titanium nitride in the tungsten carbide powder were relatively poor. As a result, the relative density of the obtained material decreased, the porosity grade increased, the average tungsten carbide grain size increased significantly, and the Vickers hardness, bending strength, and mirror polishing quality were all lower than those of Examples 1 and 2.
[0032] In Comparative Example 2, only the titanium nitride powder was subjected to surface carbonitriding treatment to form a titanium carbonitride transition layer, without further forming a tungsten carbide coating layer. Although the titanium carbonitride transition layer could still inhibit the migration of tungsten carbide grain boundaries to a certain extent, resulting in a lower average tungsten carbide grain size compared to unmodified titanium nitride, the lack of a tungsten carbide coating layer with a composition similar to that of the tungsten carbide matrix on the outside of the titanium nitride particles affected the contact and sintering bonding between the modified particles and the tungsten carbide matrix. Therefore, the relative density, Vickers hardness, and flexural strength of the obtained material were all lower than those of Examples 1 and 2, and the surface roughness after mirror polishing was also correspondingly increased.
[0033] In Comparative Example 3, the titanium nitride powder was not subjected to surface carbonitriding treatment. Instead, a tungsten carbide coating layer was directly formed on the surface of the titanium nitride particles. Although the external tungsten carbide coating layer could improve the contact state between the titanium nitride particles and the tungsten carbide matrix and promote the densification of the material to a certain extent, the lack of a titanium carbonitride transition layer between the titanium nitride core and the external tungsten carbide coating layer made it difficult to fully exert the regulatory effect of the composite interface on grain boundary migration and microstructure stability. As a result, the average tungsten carbide grain size of the obtained material was still significantly larger than that of Examples 1 and 2. At the same time, the Vickers hardness, bending strength and mirror finish quality all decreased, indicating that the titanium carbonitride transition layer and the tungsten carbide coating layer have a synergistic effect.
[0034] In Comparative Example 4, instead of the staged mixing method of premixing tungsten carbide powder with titanium carbide powder, molybdenum carbide powder, and chromium carbide powder, and then adding modified titanium nitride, all components were mixed at once and wet ball milled. This made it easier for the relatively low content of titanium carbide, molybdenum carbide, and chromium carbide to exhibit uneven local distribution in the large amount of tungsten carbide powder. At the same time, the modified titanium nitride was subjected to a high-speed ball milling environment for a long time, which easily affected the integrity and dispersion of its surface titanium carbonitride transition layer and tungsten carbide coating layer, resulting in differences in the degree of grain suppression and densification in different regions during sintering. Therefore, the material obtained in Comparative Example 4 had a lower relative density, a larger average tungsten carbide grain size, a lower Vickers hardness and flexural strength, and a higher surface roughness after mirror polishing than in Examples 1 and 2.
[0035] In Comparative Example 5, no pulse preheating and venting treatment was performed. Instead, the sintered powder was directly introduced into the subsequent SPS sintering process after being loaded into a graphite mold and evacuated. This prevented the pre-venting of residual gases between powder particles and on the powder surface, as the particle pores were not fully interconnected. With subsequent heating, pressurization, and particle shrinkage, some residual gases were easily trapped inside the sintered body, forming porosity defects. Therefore, the relative density of the material obtained in Comparative Example 5 was significantly reduced, the porosity grade increased, and the flexural strength and Vickers hardness decreased. At the same time, the internal pores were prone to forming micro-pits after mirror finishing, resulting in a significant increase in surface roughness after mirror polishing. However, the average tungsten carbide grain size changed relatively little, indicating that pulse preheating and venting mainly had a significant impact on residual porosity and material densification.
[0036] In Comparative Example 6, the axial load was not gradually increased according to the axial shrinkage state of the sintered powder during the SPS sintering process. Instead, the axial load was directly increased to 35kN after pulse preheating and degassing and maintained until the end of sintering. This caused the sintered powder to bear a large axial load at a relatively low temperature stage. Some areas were prone to premature compaction and premature closure of particle pores, which was not conducive to the continued discharge of residual gas during sintering. At the same time, the particle contact, shrinkage and densification rates in different areas were prone to differences. Therefore, the relative density, Vickers hardness and flexural strength of the material obtained in Comparative Example 6 were lower than those in Examples 1 and 2. The porosity level and average tungsten carbide grain size increased, and the surface roughness after mirror polishing also increased accordingly. This shows that graded pressurization according to the axial shrinkage state of the sintered powder is beneficial to coordinating the degassing, shrinkage and densification processes and improving the comprehensive performance of the ultra-low binder cemented carbide material.
[0037] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing an ultra-low binder hard alloy material for optical molds, characterized in that, Includes the following steps: S1. Weigh out 0.2-0.4% titanium carbide powder, 0.2-0.4% titanium nitride powder, 0.05-0.15% molybdenum carbide powder, 0.03-0.10% chromium carbide powder, 0.03-0.08% nano carbon powder, and the balance tungsten carbide powder by mass percentage. S2. Titanium nitride powder is placed in a carbon-containing atmosphere for surface carbonitriding treatment to form a titanium carbonitride transition layer on the surface of titanium nitride particles; then the surface carbonitrided titanium nitride powder is dispersed, and a tungsten source precursor and an auxiliary carbon source are added so that the tungsten source precursor is attached to the surface of the titanium carbonitride transition layer. After drying, reduction and carbonization treatment, a tungsten carbide coating layer is formed to obtain modified titanium nitride. S3. Take 15-30% of the total mass of tungsten carbide powder and premix it with titanium carbide powder, molybdenum carbide powder and chromium carbide powder to obtain a first premix; mix the first premix with the remaining 70-85% of tungsten carbide powder and nano carbon powder to obtain a mixed powder. S4. The mixed powder obtained in step S3 is subjected to wet ball milling. After ball milling, the modified titanium nitride obtained in step S2 is added and mixed. Then, the mixture is degassed, dried and sieved to obtain sintered powder. S5. The sintered powder is loaded into a graphite mold, and the graphite mold is placed in a spark plasma sintering equipment for pulse preheating and degassing under vacuum and low axial load conditions. S6. After completing the pulse preheating and exhaust in step S5, SPS sintering is carried out by segmented heating. The axial load is gradually increased according to the axial shrinkage state of the sintered powder. When the sintering temperature reaches 1700℃, the axial load is increased to 35kN and held at 1700℃ and 35kN for 20min. S7. After completing the SPS sintering in step S6, stop heating and cool down while maintaining the axial load. Gradually remove the axial load as the temperature decreases. After cooling and demolding, obtain the ultra-low binder hard alloy material for optical molds.
2. The method for preparing the ultra-low binder hard alloy material for optical molds according to claim 1, characterized in that, In step S1, the D50 particle size of the tungsten carbide powder is 0.25-0.45 μm, the D50 particle size of the titanium carbide powder is 0.08-0.20 μm, the D50 particle size of the titanium nitride powder is 0.05-0.15 μm, the D50 particle size of the molybdenum carbide powder is 0.05-0.15 μm, the D50 particle size of the chromium carbide powder is 0.05-0.15 μm, and the D50 particle size of the nano-carbon powder is 30-100 nm. Before mixing, tungsten carbide powder, titanium carbide powder, titanium nitride powder, molybdenum carbide powder and chromium carbide powder were dried in a vacuum environment at 110-140℃ for 2-5 hours, and then cooled to below 40℃ in a vacuum or high-purity argon environment and sealed for storage.
3. The method for preparing the ultra-low binder hard alloy material for optical molds according to claim 1, characterized in that, In the surface carbonitriding process of step S2, titanium nitride powder is placed in an atmosphere furnace, and a mixed gas composed of methane, hydrogen and argon is introduced into the atmosphere furnace. The volume ratio of methane, hydrogen and argon is 1:3-6:8-15. The temperature is increased to 850-1000℃ at a heating rate of 3-8℃ / min, and held at 850-1000℃ for 30-90min, so that the carbon elements produced by the decomposition of methane diffuse from the surface of the titanium nitride particles inward, and the surface layer of the titanium nitride particles is partially transformed to form a titanium carbonitride transition layer. The thickness of the titanium carbonitride transition layer is 3-15 nm.
4. The method for preparing the ultra-low binder hard alloy material for optical molds according to claim 3, characterized in that, In the dispersion and tungsten-containing precursor coating process of step S2, titanium nitride powder forming the titanium carbonitride transition layer is added to a mixture of anhydrous ethanol and deionized water, wherein the volume ratio of anhydrous ethanol to deionized water is 4-7:1, the mass fraction of titanium nitride powder in the resulting titanium nitride dispersion is 3-8%, and 0.3-0.8% of ammonium polyacrylate is added, and the mixture is sheared and dispersed at 1000-2000 rpm for 10-30 min, followed by ultrasonic dispersion for 20-40 min. Ammonium metatungstate is added to the obtained dispersion as a tungsten source precursor, wherein the mass of tungsten in the ammonium metatungstate is 5-12% of the mass of the titanium nitride powder. Then glucose is added as an auxiliary carbon source, wherein the mass of glucose added is 10-18% of the mass of the ammonium metatungstate. The mixture is stirred at 300-800 rpm for 30-90 min at 50-70℃ to allow the tungsten source precursor and auxiliary carbon source to adhere to the surface of the titanium carbonitride transition layer. After mixing, the mixture is spray-dried to obtain composite titanium nitride powder with a tungsten-containing precursor coating layer.
5. The method for preparing the ultra-low binder hard alloy material for optical molds according to claim 4, characterized in that, In the reduction and carbonization process of step S2, the composite titanium nitride powder is placed in an atmosphere furnace and heated to 500-650°C at a heating rate of 3-8°C / min under the protection of high-purity argon gas and held for 30-90 min to cause the auxiliary carbon source to pyrolyze. Subsequently, the temperature was raised to 650-800℃ and held for 1-2 hours in a reducing atmosphere composed of hydrogen and argon to reduce the tungsten source precursor in the tungsten-containing precursor coating layer to form tungsten-based particles. After the reduction treatment is completed, the temperature is raised to 900-1050℃ and a mixed gas of methane and hydrogen is introduced for carbonization treatment for 0.5-2 hours, so that the tungsten-based particles are transformed into tungsten carbide coating layer, so as to obtain modified titanium nitride with titanium nitride core, titanium carbonitride transition layer and tungsten carbide coating layer from the inside to the outside. The tungsten carbide coating has an average thickness of 5-25 nm, the volume ratio of hydrogen to argon is 1:2-5, and the volume ratio of methane to hydrogen is 1:4-10.
6. The method for preparing the ultra-low binder hard alloy material for optical molds according to claim 1, characterized in that, In step S3, 15-30% of the total mass of tungsten carbide powder is taken, and the tungsten carbide powder is premixed with titanium carbide powder, molybdenum carbide powder and chromium carbide powder at 20-50 rpm for 30-60 min to obtain the first premix. The first premixed material is mixed with the remaining 70-85% of tungsten carbide powder and nano carbon powder at 30-60 rpm for 30-90 min to obtain the mixed powder. In step S4, anhydrous ethanol is added to the mixed powder as a ball milling medium, and tungsten carbide balls are used as the grinding medium. The liquid-solid mass ratio between the anhydrous ethanol and the mixed powder is 0.6-1.0:1, and the ball-to-powder mass ratio is 3-5:
1. Wet ball milling is carried out at 120-180 rpm for 2-5 hours. After wet ball milling, add the modified titanium nitride, reduce the speed to 50-90 rpm and continue mixing for 30-90 min to disperse the modified titanium nitride between the tungsten carbide particles. After mixing, the resulting slurry is vacuum degassed for 10-30 minutes, then spray-dried, and the resulting powder is dried in a vacuum environment at 80-110℃ for 4-8 hours. Subsequently, it is sieved through a 100-200 mesh sieve to obtain the sintered powder.
7. The method for preparing the ultra-low binder hard alloy material for optical molds according to claim 1, characterized in that, In step S5, the sintered powder is loaded into the graphite mold in 2-4 batches. After each addition of sintered powder, vibration is performed to level the material. After loading is completed, an axial preload of 2-5 kN is applied and held for 1-3 minutes. The sintering chamber of the spark plasma sintering equipment is evacuated to below 20 Pa, and preheated by applying pulsed DC current under an axial load of 2-5 kN. During the temperature rise from room temperature to 500℃, the temperature is increased at a rate of 60-100℃ / min. After the temperature reaches 500℃, the temperature is increased to 850-950℃ at a rate of 70-110℃ / min, and held at 850-950℃ for 3-8 minutes, while maintaining the pressure in the sintering chamber at 5-20Pa. During the pulse preheating and venting process, the axial displacement of the pressure head on the graphite mold is monitored. Before the sintered powder produces continuous axial shrinkage, the axial load is maintained at 2-5 kN to allow the residual gas in the sintered powder to be discharged outward.
8. The method for preparing the ultra-low binder hard alloy material for optical molds according to claim 1, characterized in that, In step S6, the SPS sintering is performed using a staged pressurization method based on the axial shrinkage state: The sintering temperature was further increased from 850-950℃ to 1100-1250℃. When continuous axial displacement of the pressure head on the graphite mold was detected, the axial load was gradually increased to 6-10kN. Then, the temperature was increased to 1400℃ at a heating rate of 60-90℃ / min, and the axial load was gradually increased to 12-18kN. In the 1400-1550℃ range, the heating rate was controlled at 40-60℃ / min, and the axial load was gradually increased to 20-25kN. In the 1550-1650℃ range, the heating rate was reduced to 25-45℃ / min, and the axial load was gradually increased to 28-32kN. After the sintering temperature reaches 1650℃, the temperature is further increased to 1700℃ at a heating rate of 15-30℃ / min, and the axial load is simultaneously increased to 35kN. The temperature is then maintained at 1700℃ and 35kN for 20 minutes to allow the residual pores in the sintered powder to shrink and close.
9. The method for preparing the ultra-low binder hard alloy material for optical molds according to claim 1, characterized in that, In step S7, after SPS sintering at 1700℃ and 35kN is completed, the heating is stopped, and the axial load of 35kN is maintained for cooling. When the temperature drops to 1550-1600℃, the first pressure relief is carried out to reduce the axial load to 20-25kN, and the cooling process continues. When the temperature drops to 1350-1450℃, a second depressurization is performed to reduce the axial load to 8-12kN, and cooling continues. When the temperature drops to 1100-1200℃, the axial load is completely removed, and high-purity argon gas is introduced into the sintering chamber. The temperature is then reduced to 800℃ at a cooling rate of 2-5℃ / min, and then reduced to 500℃ at a cooling rate of 5-10℃ / min. The temperature is then cooled to room temperature with the furnace. After demolding, the ultra-low binder hard alloy material for the optical mold is obtained.
10. A low-binder hard alloy material for optical molds, characterized in that, The optical mold is prepared by the preparation method according to any one of claims 1-9. The ultra-low binder hard alloy material does not contain cobalt-based binder, has a relative density greater than 99%, a porosity grade of A02B00, and an average tungsten carbide grain size of not more than 0.6 μm.